Decision to Paving Solutions in Road Infrastructures Based on Life-Cycle Assessment - Maria de Lurdes Antunes; Vânia Marecos; José Neves; João Morgado (The Baltic Journal of Road and Bridge Engineering)
The construction and maintenance of a road network involve the expenditure of large budgets. In order to optimize the investments in road infrastructures, designers and decision makers should have the instruments to make the most suitable decision of paving solutions for each particular situation. The life-cycle assessment is an important tool of different road pavement solutions with this purpose. This paper presents a study concerning the life-cycle cost analysis of different flexible and semi-rigid paving alternatives, with the objective to contribute for a better support in the decision process when designing new pavement structures. The analysis was carried out using data on construction costs of certain typical pavement structures and taking into consideration appropriate performance models for each type of structure being selected. The models were calibrated using results from long term performance studies across Europe and the maintenance strategies considered have taken into account the current practice also found in the European context. Besides the life-cycle administration costs, the proposed methodology also deals with user and environmental costs through its inclusion in the decision process using multi-criteria analysis. It was demonstrated that this methodology could be a simple and useful tool in order to achieve the most adequate paving solutions of a road network, in terms of construction and maintenance activities, based simultaneously on technical, economic and environmental criteria.